Analisis Perencanaan Penerapan Enterprise Resource Planning (ERP) dalam Aktivitas Manajerial di Yayasan Sosial dan Pendidikan Bina Muda Cicalengka - Fathur Alhadian; Faoziah Ulfah Fatmawati (Trending: Jurnal Manajemen dan Ekonomi, 2024)
An Integrated Information System based on Enterprise Resource Planning (ERP) has become a tool that can be utilized to enhance the quality of organizational resource management, ensuring greater efficiency in achieving an organization's objectives. This research aims to analyze the technical planning aspects in the implementation plan of an ERP system within an educational foundation. The research employs a qualitative descriptive through interview techniques. The findings of this research indicate that the Bina Muda Foundation needs to prepare Hardware, Procedures, Policies, and People components among the eight main components required. The foundation's implementation plan for the new ERP can be outlined up to the fourth stage out of the ten stages, encompassing the analysis of needs, planning, ERP vendor selection, as well as configuration and adjustment. The benefits derived from the use of ERP include 1) enhancing foundation management governance, 2) expanding service sectors, 3) improving the school's image and community performance index, and 4) enhancing service quality in the education industry competition.